Analisis Kualitas dan Rasio Indikator Pencemaran Air Pada Kolam Bekas Penambangan Pasir di Desa Tewang Rangkang Kalimantan Tengah - Prayoga, Aditia (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Danau Biru” is a former sand mining pond located in Tewang Rangkang Village, Tewang Sangalang Garing Sub-district, Katingan Regency, Central Kalimantan Province. This study aims to analyze the water quality of the pond based on Government Regulation (PP) No. 22 of 2021 concerning Water Quality Standards for Lakes and to evaluate the pollution index. Water sampling was divided into primary and secondary data. Primary data included recording the coordinates of sampling points, collecting water from each predetermined site, documenting all sampling activities, and preparing accessibility, geological, and sampling point maps. Secondary data were obtained from relevant companies and institutions, including laboratory test results and supporting hydrological data. The results indicate that the pond water has been polluted, mainly due to the impact of past sand mining activities, the geological structure of the area, and local community activities. Several parameters exceeded the permissible thresholds set by PP No. 22/2021. Furthermore, the Pollution Index (PI) calculation for samples D1–D4 confirmed that the pond water is categorized as polluted across various classes of water utilization. These findings highlight the urgent need for monitoring and policy regulations regarding water management in the pond to prevent further environmental degradation.